2021
DOI: 10.21203/rs.3.rs-170697/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of Syphilis, HBV and Its Associated Risk Factors Among Pregnant Women Attending at Saint Paul’s Hospital Millennium Medical College, Addis Ababa Ethiopia

Abstract: Background: Syphilis and Hepatitis B Virus (HBV) share similar modes of transmission. Their occurrence during pregnancy has an adverse effect both on the fetus and pregnant women. The aim of this study was to determine the seroprevalence and associated risk factors of syphilis and HBV among pregnant women. Methods: A cross-sectional study was undertaken from July to September 2019 in 290 pregnant women at Saint Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia. Gestational and socioeconomic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ]. Some other research findings in Ethiopia and abroad revealed that the seroprevalence of HBV among the same study subjects was lower than that of the current study [ 6 , 13 , 19 , 20 , 34 ]. On the contrary, some other studies showed higher HBV infection rate among different population groups and among pregnant mothers.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ]. Some other research findings in Ethiopia and abroad revealed that the seroprevalence of HBV among the same study subjects was lower than that of the current study [ 6 , 13 , 19 , 20 , 34 ]. On the contrary, some other studies showed higher HBV infection rate among different population groups and among pregnant mothers.…”
Section: Discussioncontrasting
confidence: 77%
“…A study conducted in Pakistan showed a history of surgical procedure, and maternal age determines the prevalence of HCV [19]. Even though it is not statistically supported, the prevalence of both HBV and HCV was higher among pregnant women who are living in the rural area [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…19 However, there are still many cases of Rh D incompatibility, and it is still a public health problem in developing countries like Ethiopia, despite advances in prevention and treatment. 4 20 21 Different studies from various countries found that the prevalence of women who know about Rh-incompatibility is approximately 39% in Nigeria, 22 Saudi Arabia, 23 Addis Ababa, Ethiopia 24 and Turkey. 25 The age of mothers, income, their education level, how many pregnancies they have had and any complications they experienced during previous deliveries can all affect women's knowledge and attitude about Rh-negativity.…”
Section: Bmj Public Healthmentioning
confidence: 99%
“…Poor level of knowledge about Rh-incompatibility: if women scored less than the mean value of knowledge-related items. 24 Positive attitude toward Rh blood group screening: women who scored higher than the mean value (>42) on all attitude-related questions. 24 Negative attitude toward Rh blood group screening: women who scored lower than the mean value.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation